Fungal Metabolites for Assessment of Ganoderma Boninense Pat. Infection in Oil Palm - Lieu, Roger Toh Choon (2011)

(untitled)
Basal Stem Rot (BSR) caused by Ganoderma boninense is a serious disease in oil palm. Detection of BSR is based mainly on visible symptoms, and confirmed by plating infected tissues on Ganoderma selective media. Unfortunately, these symptoms are only visible when at least half of the basal tissue has been infected. Current research on the plant-pathogen interaction showed that invasion by pathogens can lead to increase of fungal biomass in the healthy plant, making it detectable during the infection. Certain primary fungal metabolites were targeted as they were produced abundantly during the reproduction of mycelium. Therefore, based on the mode of infection and spread of G. boninense on oil palm, the probable strategy is to unravel the metabolic pathway of the plant upon infection and possibly use this approach to differentiate between healthy and infected palms at the early stage of infection. The technique used for analysis and identification of the targeted metabolites were Thin Layer Chromatography (TLC), Ultra Performance Liquid Chromatography (UPLC), Gas Chromatography coupled with Mass Spectrometry (GCMS) and Nuclear Magnetic resonance (NMR). This research focused on the potential of detecting targeted metabolites as indicators for Ganoderma infection in field palms. Metabolites from G. boninense were extracted and used as indicator for TLC and UPLC analysis. Eighty healthy oil palm seedlings were used as control where no artificial infection applied while eighty seedlings for artificial infection. Metabolites for healthy and infected palms were extracted from root tissues of the experimental seedlings. Meanwhile, two random samplings for the healthy and Ganoderma-infected stem tissues were carried out from MPOB Experimental Station, Kluang, Johor and Sime Darby oil palm plantation from Banting, Selangor. By using the same extraction method, these samples were analyzed by TLC with optimum combination of solvent systems to detect and the quantification of the metabolites was done with UPLC with progressive development of BSR symptoms. G. boninense extract was used as indicator for TLC and UPLC analysis to distinguish between healthy and infected oil palm samples. Results showed that the best combination solvent system which gave the clearest spot separation were acetone and hexane in the ratio of 30:70. Round and clear separated spots representing different metabolites were detected. Compared with pure G. boninense extract as indicator, four clear spots were consistently detected in infected tissues extracts which however were not detected in healthy tissues extracts. These spots could be used to distinguish between healthy and infected tissues. Two clearest spots were chosen for further analysis named as metabolite A and metabolite B. In UPLC, it showed that metabolites A and B were increased exponentially and showed a positive correlation of the disease severity with time. Metabolites A and B were purified and sent for GCMS for their molecular weight followed by NMR analysis for chemical structure identification. Based on the results from GCMS and NMR, it was concluded that metabolite B was identified to be ergosterol which played an important role in fungal cell wall development. Meanwhile, metabolite A was tentatively suggested to be 2,4-ditert-butylphenol. According to the present work, it could be concluded that Ganoderma infection in palms increase the production of metabolites which could be used as indicators for early detection of infection in oil palms. Further studies are needed to produce a better implementation of this finding as disease diagnostic tool in the commercialized oil palm field.